Dynamics of Structural and Functional Changes of Patients with Dry Form Age-related Macular Degeneration after Double Filtration Plasmapheresis - A. A. Volozhev; A. N. Kulikov; A. N. Belskih; D. S. Maltsev; S. E. Bednova; E. N. Nikolaenko (Oftalʹmologiâ)
Actuality. One of the significant ophthalmic diseases is a dry form age-related macular degeneration (dAMD). The issues of etiology and pathogenesis are not completely cleared nowadays and they signify the subject of discussion. There are risk factors of dAMD (age, heredity, lifestyle etc.) which can cause metabolic disorders, changes hemorheological parameters which promote activation of druseogenesis and as a result an angiogenesis. Mostly an outcome of dAMD is geographical atrophy and decrease of central visual acuity. At the same time, it is known that similar metabolic and rheological disorders detected in other diseases are effectively corrected by extracorporeal rheoaferesis, in particular, using double filtration plasmapheresis. Thus, using of extracorporeal rheoaferesis with dAMD patients is pathogenetically well-reasoned, but in the available literature, a correct analysis of the effectiveness and safety of double filtration plasmapheresis in patients with intermediate stage of dAMD is presented poorly.Objective. To study along with data of OCT, OCT angiography, visometry, microperimetry and electroretinography structural and functional changes in the macular zone in patients with a dry form of age-related macular degeneration after the using of double filtration plasmapheresis.Patients and methods. The study included 63 patients (94 eyes) with an intermediate stage of dAMD. The patients were separated into two groups randomly. The first (main) group included 34 patients (52 eyes) who were performed double filtration plasmapheresis (DFPP) on an OctoNova device using a Plasmaflo plasma filter and a Cascadeflo EC40 fractionator in the amount of 4 procedures with a frequency of 1 time per week for 1 month. The second group (control) included 29 patients (42 eyes) who did not receive any specific treatment. In the main group of patients, OCT, OCT angiography, microperimetry and electroretinography were additionally performed in addition to standard ophthalmological examination before the DFPP course, after the DFPP course (1 month after the start of follow-up), 6 and 12 months later. Patients in the control group also underwent a similar examination at the specified time — 1, 6, 12 months after the start of follow-up.Results. In this study we found according to optical coherence tomography, optical coherence tomography-angiography, visometry, microperimetry and electroretinography, positive dynamics of structural and functional parameters of the macular retina is observed in patients with a dry form of age-related macular degeneration with using double filtration plasmapheresis. At the same time, a statistically significant difference between the two groups begins at 1 month and persists for 12 months of follow-up, which points to stabilization of the pathological process during the specified period.Conclusions. This study showed that after applying the double filtration plasmapheresis in patients with dry form of age-related macular degeneration, there is an improvement in structural and functional parameters of the macular zone, consisting in a decrease volume DOPES and stabilization of retinal light sensitivity.